2012
DOI: 10.1208/s12248-012-9439-1
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Levodopa, Carbidopa, and 3-O-Methyldopa Following 16-hour Jejunal Infusion of Levodopa-Carbidopa Intestinal Gel in Advanced Parkinson’s Disease Patients

Abstract: Abstract. Motor complications of Parkinson's disease (PD) are a consequence of pulsatile dopaminergic stimulation from standard oral levodopa therapy. Levodopa-carbidopa intestinal gel (LCIG) is infused continuously via an intrajejunal percutaneous gastrostomy tube. This was the first study designed to characterize the full pharmacokinetic profiles of levodopa, carbidopa, and levodopa metabolite, 3-Omethyldopa (3-OMD) with 16-h LCIG infusion. Nineteen advanced PD patients (mean age, 65 years) who were on LCIG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 43 publications
4
80
0
Order By: Relevance
“…Pharmacokinetic studies show LCIG jejunal infusion provides relatively constant plasma levodopa levels with less variability than oral formulations, 14,15 and open label studies report a marked reduction (improvement) in “Off” time without worsening of dyskinesias. 1619 Despite the lack of double blind trials, LCIG is approved for use in 43 countries.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacokinetic studies show LCIG jejunal infusion provides relatively constant plasma levodopa levels with less variability than oral formulations, 14,15 and open label studies report a marked reduction (improvement) in “Off” time without worsening of dyskinesias. 1619 Despite the lack of double blind trials, LCIG is approved for use in 43 countries.…”
Section: Introductionmentioning
confidence: 99%
“…Jejunal infusion of levodopa/carbidopa gel, allowing fine-tuning of doses [5] which reduces motor fluctuations in patients with advanced PD [6], has demonstrated the importance of individualized doses and a stable plasma concentration [7]. In theory, oral levodopa administration could have similar effects, up to a certain degree, when administered more frequently, but it is difficult to adhere to [8].…”
Section: Introductionmentioning
confidence: 99%
“…Levodopa given orally or directly in the duodenum is absorbed in the proximal one-third of the small intestine and therefore the gastric emptying (GE) is one factor affecting the uptake of orally given levodopa (24). The GE has been shown to be delayed in PD patients (25)(26)(27)(28)(29)(30) resulting in an impaired bioavailability of levodopa (31)(32)(33)(34).…”
Section: Levodopa In the Peripherymentioning
confidence: 99%
“…Orally given levodopa is absorbed in the proximal one-third of the small intestine and, except for the competition between levodopa and other LNAAs across the intestinal mucosa (35,36), GE is an important factor (24). It has been shown that more than 70 % of PD patients suffer from impaired gastric motility (27,31) with symptoms like early satiety, postprandial bloating and nausea and it has been suggested that this is caused by the delay in GE that has been shown in PD patients (25)(26)(27)(28)(29)(30)(136)(137)(138).…”
Section: Gastric Emptyingmentioning
confidence: 99%